Counting on a cowboy - Richardson, Sara (Romance fiction writer) (Richardson, Sara (Romance fiction writer). Star Valley novel., 2024)
When retired SEAL-turned-bronc rider Thatch Hearst hires her to get him ready for the big leagues, yoga instructor Lyric Valenza, who has vowed never to need a man, is faced with her toughest challenge yet when she realizes there's a difference between needing and wanting someone--and she wants him.